2009
DOI: 10.1007/s00540-009-0797-5
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of blood volume control system and its implications in perioperative fluid management

Abstract: The use of fluid therapy attempts to optimize blood circulation by manipulating the circulating blood volume (BV). BV may be a key intermediate parameter between fluid therapy and the blood circulation, and it has been assumed that BV can be controlled by fluid therapy. In order to construct a fluid therapy protocol, firstly, we have to confirm whether BV can actually be controlled by fluid therapy. Volume kinetics studies and dilution techniques for BV measurements have enabled the actual effects of fluid man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…In our opinion, conventional Doppler indices are better and more robust for this purpose than TDI. Thus, in MO, monitoring ΔSV together with conventional dynamic transmitral indices provides sufficient information about volumeresponsiveness, limitations in global stressed volume, and pressure-volume relationship in LV (22,27). In addition, we confirmed that where there are physical limitations for signal acquisition related to body habitus as in MO, detailed comprehensive assessment of filling pressures can be difficult and time-consuming.…”
Section: Discussionsupporting
confidence: 60%
“…In our opinion, conventional Doppler indices are better and more robust for this purpose than TDI. Thus, in MO, monitoring ΔSV together with conventional dynamic transmitral indices provides sufficient information about volumeresponsiveness, limitations in global stressed volume, and pressure-volume relationship in LV (22,27). In addition, we confirmed that where there are physical limitations for signal acquisition related to body habitus as in MO, detailed comprehensive assessment of filling pressures can be difficult and time-consuming.…”
Section: Discussionsupporting
confidence: 60%
“…Where Qf is the total fluid flux out of capillaries (not represent the quantity, but just the speed of water movement [16]) and Kf is the filtration coefficient (the product of the membrane conductance and the membrane surface area), Pc is intravascular hydrostatic pressure, Pi is interstitial hydrostatic pressure, πc is colloid osmotic pressure within the vasculature, πi is interstitial colloid osmotic pressure gradient across the vessel wall, and R is the oncotic reflection coefficient, the tendency of a membrane to impede the passage of oncotically active particles [16,41]. A R of 0 indicates a membrane that is totally permeable to protein while a R of 1 indicates a membrane that completely prevents protein diffusion.…”
Section: Fluid Physiologymentioning
confidence: 99%
“…Distribution terminates when the balance of the hydrostatic pressure and the osmotic pressure cancel each other out. Because the interstitium consists not only of free space but also of absorbent gel, captured water in the gel does not contribute to lowering the osmotic pressure in the interstitium [16]. Therefore, the osmotic pressure does not easily change until the gel is saturated by water movement.…”
Section: Fluid Physiologymentioning
confidence: 99%
See 2 more Smart Citations